2010
DOI: 10.1063/1.3428956
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the As2/As4 growth modes on the formation of quantum dot-like InAs islands grown on InAlGaAs/InP (100)

Abstract: The formation process of InAs quantum dashes and quantum dots (QDs) grown on quaternary InAlGaAs surfaces lattice-matched to n-type InP(100) are investigated. A clear trend of the InAs to form dashes or dots depending on the species of supplied arsenic could be demonstrated. Using As4, elongated quantum dashes can be observed. Changing the growth mode to As2 molecules enables a shape transition from dashes to dome-shaped QDs. The dot ensembles exhibit improved photoluminescence (PL) intensity and linewidth ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 13 publications
0
26
0
1
Order By: Relevance
“…Recently, in an attempt to realize InAs Qdots on (100) InP using MBE, Gilfert et al [45] found that the arsenic species had a dramatic effect on the formation of nanostructures on InGaAlAs buffer layer. The As 4 supply during InAs deposition resulted in Qdash formation on InGaAlAs whereas As 2 supply produced round-shaped Qdots structures with density 2.0×10 10 cm -2 , as shown in Figs.…”
Section: Qdots On (100) Inp Substratementioning
confidence: 99%
“…Recently, in an attempt to realize InAs Qdots on (100) InP using MBE, Gilfert et al [45] found that the arsenic species had a dramatic effect on the formation of nanostructures on InGaAlAs buffer layer. The As 4 supply during InAs deposition resulted in Qdash formation on InGaAlAs whereas As 2 supply produced round-shaped Qdots structures with density 2.0×10 10 cm -2 , as shown in Figs.…”
Section: Qdots On (100) Inp Substratementioning
confidence: 99%
“…So far only a few studies regarding InAs QDs on lattice matched InGaAlAs as a buffer layer have been reported [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…10 that the detected CER signal is the order of 10 -5 DR/R. When an InAs layer is deposited on an InP substrate both regular QDs and elongated QDs (so called quantum dashes) can be formed depending on the growth conditions [52]. For both QDs and quantum dashes (QDashes) a wet− ting layer is formed but the quantum confinement for elec− trons is much weaker for InAs/InP system than for InAs/ GaAs one due to a smaller conduction band offset at the InAs/InP interface.…”
Section: Quantum Dots and Dashesmentioning
confidence: 99%